Functional anatomy of the vagus system – Emphasis on the somato-visceral interface - Neuhuber, Winfried; Berthoud, Hans Rudolf (Autonomic Neuroscience-Basic & Clinical, 2021)
Due to its pivotal role in autonomic networks, the vagus attracts continuous interest from both basic scientists and clinicians. In particular, recent advances in vagus nerve stimulation strategies and their application to pathological conditions beyond epilepsy provide a good opportunity to recall basic features of vagal peripheral and central anatomy. In addition to the “classical” vagal brainstem nuclei, i.e., dorsal motor nucleus, nucleus ambiguus and nucleus tractus solitarii, the spinal trigeminal and paratrigeminal nuclei come into play as targets of vagal afferents. On the other hand, the nucleus of the solitary tract receives and integrates not only visceral but also somatic afferents. Thus, the vagus system participates significantly in what may be defined as “somato-visceral interface”.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Auricular nerves; Dorsal motor nucleus; Nucleus ambiguus; Nucleus tractus solitarii; Paratrigeminal nucleus; Vagus nerve stimulation